Empowering Talent In The Age Of Artificial Intelligence: Innovations In Human Resource Management - Ekawahyu Kasih; Farah Qalbia; Novrizal Novrizal (International Forum of Researchers and Lecturers, 2022)
In the dynamic landscape of Human Resource Management (HRM), the emergence of Artificial Intelligence (AI) technologies presents both challenges and opportunities. This research aims to explore strategies for empowering talent amidst AI innovations in HRM. The research adopts a phenomenological approach to delve into the lived experiences of HR professionals and employees within organizations integrating AI technologies. Through purposive sampling, data were collected via in-depth interviews and focus group discussions. Thematic analysis was employed to identify patterns, themes, and insights from the narratives. The findings reveal a nuanced understanding of how AI impacts talent management practices, including recruitment, training, performance evaluation, and career development. Moreover, the research elucidates the importance of human-centric approaches in leveraging AI to augment rather than replace human capabilities. These insights contribute to enhancing organizational strategies for talent empowerment in the era of AI-driven HRM innovations.